2018
DOI: 10.7150/jca.26044
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of treatment plan quality of VMAT for esophageal carcinoma with: flattening filter beam versus flattening filter free beam

Abstract: Purpose: To investigate the difference in treatment plan quality of volumetric modulated arc treatment (VMAT) for esophageal carcinoma with flattening filter beam (FF) and flattening filter free beam (FFF).Material and methods: A total of fifty-six treatment plans were generated for twenty eight esophageal carcinoma patients with flattening filter beam and flattening filter free beam, using same optimal parameters. The homogeneity index (HI) and conformal index (CI) of targets, and some special points on Dose-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
4
8
0
Order By: Relevance
“…Because the FFF mode requires more MUs for a point in a segment far away from the central axis to achieve the same depth dose as the point in the central, the average total MUs for FFF‐VMAT plans was greater than that of the FF‐VMAT plans. This finding is in line with the results from previous studies 19,25,26 . However, there was no significant difference observed in the plan quality among the two beam modes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Because the FFF mode requires more MUs for a point in a segment far away from the central axis to achieve the same depth dose as the point in the central, the average total MUs for FFF‐VMAT plans was greater than that of the FF‐VMAT plans. This finding is in line with the results from previous studies 19,25,26 . However, there was no significant difference observed in the plan quality among the two beam modes.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is in line with the results from previous studies. 19,25,26 However, there was no significant difference observed in the plan quality among the two beam modes.…”
Section: Discussionmentioning
confidence: 85%
“…The maximum dose and near max dose to the PTV was higher in the FFF mode but the mean dose was less in comparison with the FF mode which was found by many authors like Sun et al 24 Our study showed that the treatment planning with FFF beams resulted in plans of equal quality in terms of PTV coverage compared with flattened beams. No significant differences were found in dose coverage for PTV in both plans.…”
Section: Discussionsupporting
confidence: 71%
“…The reduction of delivery time in the application of VMAT compared to IMRT was also found in the same order for other entities [12,18,49], using the same equipment. Most comparisons of FB and FFF in these studies and also [29] found shorter or statistically not significantly different DTs for FFF. Treutwein et al [18] discussed that additional MU are required to compensate the profile fall off which also takes additional time.…”
Section: Plan Qualitymentioning
confidence: 48%
“…It supports an improvement of the conformity. The same set of dose volume objectives has been used for all plans to get comparable results [12,18,28,29]. The aim of this set was to keep the risk for the OARs on an acceptable level, but to leave freedom for the optimizer to achieve good conformity and homogeneity.…”
Section: Treatment Planningmentioning
confidence: 99%